1995
DOI: 10.1074/jbc.270.5.1983
|View full text |Cite
|
Sign up to set email alerts
|

A New Old Yellow Enzyme of Saccharomyces cerevisiae

Abstract: In 1993, the first gene of Old Yellow Enzyme (OYE) of Saccharomyces cerevisiae was cloned (Stott, K., Saito, K., Thiele, D. J., and Massey, V. (1993) J. Biol. Chem. 268, 6097-6106) and named OYE2 to distinguish it from the first OYE gene cloned from Saccharomyces carlsbergenesis (Saito, K., Thiele, D. J., Davio, M., Lockridge, O., and Massey, V. (1991) J. Biol. Chem. 266, 20720-20724). The analysis of an OYE2 deletion mutant suggested that S. cerevisiae had at least two OYE genes. In the present study, we clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 29 publications
4
78
0
Order By: Relevance
“…carlsbergensis (OYE1), 14) Sac. cerevisiae (OYE2, OYE3), 15,16) and Schizosaccharomyces pombe (OYEA, OYEB), 17) and estrogen-binding protein of Candida albicans (EBP1) 18) are aligned. Gaps in the aligned sequences are indicated by dashes (").…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…carlsbergensis (OYE1), 14) Sac. cerevisiae (OYE2, OYE3), 15,16) and Schizosaccharomyces pombe (OYEA, OYEB), 17) and estrogen-binding protein of Candida albicans (EBP1) 18) are aligned. Gaps in the aligned sequences are indicated by dashes (").…”
Section: Discussionmentioning
confidence: 99%
“…An Old Yellow Enzyme was isolated from brewers' yeast as theˆrst ‰avoprotein by Warburg and Christian, 19,20) and has been thoroughly studied by many researchers. [13][14][15][16][21][22][23] However, the application of an Old Yellow Enzyme to a stereospeciˆc reaction, as described here, had not been previously reported. The discovery of this stereospeciˆc reaction by Old Yellow Enzyme might help in elucidation of its reaction mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…105 Both genes are probably involved in sterol metabolism 188 NADPH is the electron donor to OYEs but the physiological electron acceptors are still unknown. It has been suggested that OYE3 forms H 2 O 2 in the presence of oxygen and NADPH, 144 and that at least one of the two OYEs may contribute to the oxygen consumption observed in the cytosolic fraction. 87,94 However, oxygen is now considered to be an opportunist electron acceptor, as are ferricyanide and methylene blue.…”
Section: Old Yellow Enzymes (Oye23)mentioning
confidence: 99%
“…Two isozymes of OYE from Saccharomyces cerevisiae, OYE2 and OYE3, which are 91 and 81% identical with the OYE from brewers' bottom yeast, respectively, have been cloned and characterized (8,15). Based on the results of the S. cerevisiae genome sequencing project, it has been established that yeast contains only these two OYE isozymes (16,17).…”
mentioning
confidence: 99%